2019
DOI: 10.1194/jlr.m093971
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of diagnostic performance of five urinary cholesterol metabolites for Niemann-Pick disease type C

Abstract: acetylglucosamine; HQC, high quality control; LC/MS/MS, liquid chromatography/tandem mass spectrometry; LQC, low quality control; MQC, middle quality control; NPC, Niemann-Pick disease type C; NPC1, NPC intracellular cholesterol transporter 1; NPC2, NPC intracellular cholesterol transporter 2; Niemann-Pick disease type C; S7B-Δ 5-CA, 3β-sulfooxy-7β-hydroxy-5-cholen-24-oic acid; S7O-Δ 5-CA, 3β-sulfooxy-7-oxo-5-cholen-24-oic acid; SNAG-Δ 5-CA, nonamidated 3βsulfooxy-7β-N-acetylglucosaminyl-5-cholen-24-oic acid; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(45 citation statements)
references
References 26 publications
(28 reference statements)
0
45
0
Order By: Relevance
“…However, more recently, a larger study performed by the same research group demonstrated upregulations in 3β-sulfoxy-7βhydroxy-5-cholen-24-oic acid and its glycine and taurine conjugates, using urine samples from NPC patients (n = 23) and control (n = 28) participants [19]. A further investigation with control (n = 38) and NPC patients (n = 28) found similar findings with an AUROC value > 0.92 for 3β-sulfoxy-7β-hydroxy-5-cholen-24-oic acid, 3β-sulfoxy-7-oxo-5-cholen-24-oic acid, non-amidated 3β-sulfooxy-7β-Nacetylglucosaminyl-5-cholen-24-oic acid, glycine-amidated 3β-sulfoxy-7β-N-acetylglucosaminyl-5cholen-24-oic acid, and taurine-amidated 3β-sulfoxy-7β-N-acetylglucosaminyl-5-cholen-24-oic acid [20]. The most significant marker with an AUROC value of 1.0 was 3β-sulfooxy-7β-hydroxy-5-cholen-24-oic acid [20].…”
Section: Niemann-pick Diseasesmentioning
confidence: 99%
See 3 more Smart Citations
“…However, more recently, a larger study performed by the same research group demonstrated upregulations in 3β-sulfoxy-7βhydroxy-5-cholen-24-oic acid and its glycine and taurine conjugates, using urine samples from NPC patients (n = 23) and control (n = 28) participants [19]. A further investigation with control (n = 38) and NPC patients (n = 28) found similar findings with an AUROC value > 0.92 for 3β-sulfoxy-7β-hydroxy-5-cholen-24-oic acid, 3β-sulfoxy-7-oxo-5-cholen-24-oic acid, non-amidated 3β-sulfooxy-7β-Nacetylglucosaminyl-5-cholen-24-oic acid, glycine-amidated 3β-sulfoxy-7β-N-acetylglucosaminyl-5cholen-24-oic acid, and taurine-amidated 3β-sulfoxy-7β-N-acetylglucosaminyl-5-cholen-24-oic acid [20]. The most significant marker with an AUROC value of 1.0 was 3β-sulfooxy-7β-hydroxy-5-cholen-24-oic acid [20].…”
Section: Niemann-pick Diseasesmentioning
confidence: 99%
“…A further investigation with control (n = 38) and NPC patients (n = 28) found similar findings with an AUROC value > 0.92 for 3β-sulfoxy-7β-hydroxy-5-cholen-24-oic acid, 3β-sulfoxy-7-oxo-5-cholen-24-oic acid, non-amidated 3β-sulfooxy-7β-Nacetylglucosaminyl-5-cholen-24-oic acid, glycine-amidated 3β-sulfoxy-7β-N-acetylglucosaminyl-5cholen-24-oic acid, and taurine-amidated 3β-sulfoxy-7β-N-acetylglucosaminyl-5-cholen-24-oic acid [20]. The most significant marker with an AUROC value of 1.0 was 3β-sulfooxy-7β-hydroxy-5-cholen-24-oic acid [20]. The sensitivity and specificity of these biomarkers, and how treatments can use the biomarkers to provide diagnostic information, needs to be explored.…”
Section: Niemann-pick Diseasesmentioning
confidence: 99%
See 2 more Smart Citations
“…A simultaneous analytical method for SNAG-Δ 5 -CA, SNAG-Δ 5 -CG, SNAG-Δ 5 -CT, S7B-Δ 5 -CA, and S7O-Δ 5 -CA in urine was developed using LC/MS/MS, and its diagnostic performance for NPC was evaluated [83]. Along with other previous reports [66,67,81,82], a LC/ESI-MS/MS system equipped with a column switching system was used.…”
Section: Abnormal Cholenoic Acidsmentioning
confidence: 99%